Legal Consequences of the Merger of Companies on the Implementation of Guarantee Function of Mortgage - Halim Ady Kurniawan; Widhi Handoko; Jawade Hafidz; Lathifah Hanim (Sultan Agung Notary Law Review, 2022)
This study aims to: 1) Knowing and analyzing the execution of mortgage guarantees due to the company merger, 2) Knowing and analyzing the legal consequences of the merger on mortgage holders to be executed, 3) Knowing the deed of settlement resulting from the company merger on the implementation of the mortgage guarantee function. The research method used empirical juridical, namely by collecting data or statutory regulations, as well as conducting interviews with related respondents. The specifications used in this study were descriptive analysis. Researchers used empirical specifications with primary and secondary data. The primary data used were obtained directly through the opinions and statements of the respondents through interviews and the reality in the field through observation. The secondary data used by the researcher is carried out by conducting a literature study by reviewing, analyzing and then processing it into a descriptive narrative so that it is easy to understand when read. The data analysis method used by researchers from the stages of primary and secondary data obtained would be descriptive-qualitative analysis. Based on the research, it can be concluded that the legal consequences of the company merger on the implementation of the mortgage guarantee function of the old company that had merged did not renew the credit agreement and mortgage certificate after the merger, so that the new company could not carry out the execution due to the negligence of the old company. Even though the guarantee is in the old company's control, the bank is only the seller of the goods, it remains the property of the debtor so that it is against propriety and violates the rights of the owner of the goods if the bank violates it by selling cheap prices. In accordance with developments in Indonesia after the birth of the Mortgage Law, the grosse deed is still maintained by introducing the mortgage certificate which also uses irah-irah so that it has executive power.